2016
DOI: 10.3389/fevo.2016.00006
|View full text |Cite
|
Sign up to set email alerts
|

An Organismal Perspective on the Evolution of Insect Societies

Abstract: Insect societies, i.e., the colonies of eusocial ants, bees, wasps, and termites, have been likened to multicellular organisms for more than a century. This framework of "superorganisms" has to date largely been used as a mechanistic description of colony functioning, or as an example of an evolutionary transition in individuality. Here I take the superorganismal view a step further, and explore what can potentially be gained if we truly accept insect societies as organisms. I suggest ways to test evolutionary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 108 publications
(158 reference statements)
1
36
0
Order By: Relevance
“…However, these reviews left the connection with superorganismality open‐ended, and Boomsma (, p. 2) erroneously credited Batra (1966 a ) for defining eusociality as being based on morphological caste differentiation. After our present historical analysis of eusociality and superorganismality, the conclusion must be that hypersociality sensu Batra () and obligate eusociality sensu Crespi & Yanega () and Boomsma (, , ) are functionally identical to superorganismality sensu Wheeler (), defined by permanent membership of each colony member to a single morphologically distinct adult caste that is fixed for life during early individual development (Wheeler, ; Helanterä, ) (Fig. ; Table , qE4, qE17, qE21, qE22, qS3, qS6 and qS7).…”
Section: Historymentioning
confidence: 97%
“…However, these reviews left the connection with superorganismality open‐ended, and Boomsma (, p. 2) erroneously credited Batra (1966 a ) for defining eusociality as being based on morphological caste differentiation. After our present historical analysis of eusociality and superorganismality, the conclusion must be that hypersociality sensu Batra () and obligate eusociality sensu Crespi & Yanega () and Boomsma (, , ) are functionally identical to superorganismality sensu Wheeler (), defined by permanent membership of each colony member to a single morphologically distinct adult caste that is fixed for life during early individual development (Wheeler, ; Helanterä, ) (Fig. ; Table , qE4, qE17, qE21, qE22, qS3, qS6 and qS7).…”
Section: Historymentioning
confidence: 97%
“…We showed that when dynamic properties of resource allocation are considered, sex allocation conflict can substantially affect colony ontogeny, and thus overall patterns of growth and productivity. Helanterä (2016) has argued that life-history trade-offs may be easier traits to conceptualize as organismal traits (i.e. traits evolving like group-selected adaptations), as opposed to traits more heavily contingent on conflicts among genes in different individuals, such as traits involving sex allocation and dispersal behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Evolution of caste‐biased gene expression in social insects has interesting similarities to evolution of tissue‐specific gene expression. Indeed, if an insect society is seen as a superorganism, queens and workers are analogous to reproductive and somatic tissues, respectively (Helanterä ). As with social insect castes, it seems that genes with a tissue‐specific expression profile are prone to fast evolution due to low pleiotropic constraint (Duret et al.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution of caste-biased gene expression in social insects has interesting similarities to evolution of tissue-specific gene expression. Indeed, if an insect society is seen as a superorganism, queens and workers are analogous to reproductive and somatic tissues, respectively (Helanterä 2016). As with social insect castes, it seems that genes with a tissue-specific expression profile are prone to fast evolution due to low pleiotropic constraint (Duret et al 1999), but it remains an open question whether genes with little constraint have been co-opted into tissue-specific expression pattern or whether the evolutionary rates have increased after the expression patterns have changed.…”
Section: Stability Of Expression Patternmentioning
confidence: 99%